Possible Pharmacological Approach Targeting Endoplasmic Reticulum Stress to Ameliorate Leptin Resistance in Obesity - Hosoi, Toru; Ozawa, Koichiro (Frontiers in Endocrinology, 2016)
Obesity is associated with metabolic syndrome, such as diabetes, hypertension, and hyperlipidemia. Therefore, drug development for the treatment of obesity is needed. Leptin is an anti-obesity hormone that inhibits food intake and increases energy metabolism, and, as such, treatments involving leptin were expected to be beneficial for obesity; however, since most obese patients are in a state of leptin resistance, these treatments may not be useful. Therefore, the amelioration of leptin resistance has recently been attracting interest as a treatment for obesity. The mechanisms underlying the development of leptin resistance need to be elucidated in more detail. Endoplasmic reticulum (ER) stress was recently suggested to be involved in the pathogenesis of leptin resistance. The molecular mechanisms responsible for leptin resistance and possible pharmacological treatments for obesity have been discussed herein, with a focus on ER stress.